Mechanochemistry: A Resurgent Force in Chemical Synthesis - Mukherjee, Nirmalya (Synlett, 2024)
Mechanochemistry, a solvent-free approach that harnesses mechanical energy, is emerging as a transformative technique in modern chemistry. It has emerged from a niche technique to a versatile tool with broad applications. By inducing physical and chemical transformations, it enables the synthesis of complex molecules and nanostructured materials. Recent advancements have extended its applications beyond simple physical transformations to encompass catalytic processes, unlocking new possibilities for selective synthesis and product design. This account delves into the fundamentals of mechanochemistry and its applications in organic synthesis, also beyond traditional synthetic routes. Mechanochemistry offers new avenues for molecular and materials discovery, expanding the scope of accessible chemical space.1 Introduction2 Organic Synthesis in Ball Mills3 Combination with Different Energy Sources4 Advantages of Mechanochemistry5 Future of Mechanochemistry6 Conclusion
Keywords: mechanochemistry; organic synthesis; solvent-free reactions; catalysis; green chemistry